Práctica de enseñanza de Lenguaje en Educación General Básica, análisis de caso en Segundo Año en la Unidad Educativa Universal Misionera del cantón Quito - Inaquiza Quishpe, Jenny Elizabeth (2016)
This research work that was made with the type of case where analysis is intended to explain the practice of teaching being applied in the area of language and literature in the second year of basic education in the Universal Missionary Education Unit ' 'CEUM'' located in the canton Quito. The approach that we have been able to provide the research corresponds to the methodological and pedagogical process applied in school hours the area of language arts. An explanation of the pedagogical models for this study are the most relevant and important is made, it is necessary to highlight the knowledge and use that teachers are giving to the document Updating and Strengthening Curriculum which of course must have at its disposal to lean on him and so properly fulfill their classes with the use of a methodological process based on observation of twenty hours of class in which he must complete a form with the following organization: general data for the date, place, subject and time , then you must complete the following categories: planning, methodological class structure, work organization of the course, student teacher interaction, assessment strategies, types and assessment tasks and observations, these fields must be completed very carefully to prune highlight the problems they may encounter. You can review the systematization of information obtained, then the conclusions it has reached after having done all the analysis of case become apparent.